Cancer-associated fibroblasts in cholangiocarcinoma: the central nexus of tumor-stroma crosstalk and therapeutic translation - Rui, Shaozhen; Liu, Yuqi; Zhao, Yongqing; Zhu, Xiaoliang; Liao, Shanhui; Zhou, Wence (Frontiers in Immunology, 2025)
Cholangiocarcinoma (CCA) is a highly invasive malignant tumor of the biliary tract, and its detection is commonly delayed until advanced stages owing to a lack of early symptoms, with dismal overall survival and a high propensity for chemoresistance. CCA is primarily classified based on its anatomical location, encompassing distinct molecular subtypes with both intertumoral and intratumoral heterogeneity. Beyond malignant epithelial cells, CCA harbors a complicated and dynamically evolving tumor microenvironment (TME), in which multiple stromal cell types orchestrate disease progression through intricate crosstalk networks. Among them, cancer-associated fibroblasts(CAFs) constitute the numerically predominant cellular component in the matrix of CCA, playing pivotal roles in extracellular matrix remodeling, immune regulation, angiogenesis, and metastasis. Traditionally regarded as predominantly tumor-promoting, CAFs have recently been recognized as a heterogeneous population with transcriptionally and functionally distinct subsets, some of which may even exert tumor-suppressive functions. Deciphering the complex biology of CAFs is crucial for advancing CCA therapy. This review provides a thorough examination of the origins, functions, and pro-tumorigenic mechanisms of CAFs in the CCA TME, alongside a critical evaluation of advancements and obstacles in the development of therapies targeting CAFs.